Assessing the recovery of immune proteins from mummified soft tissue versus archaeological bones - Paasikivi, Sofia; O'Sullivan, Ronan James; Nordfors, Ulla; Liira, Anne-Mari; Lanigan, Liam Thomas; Schuenemann, Verena J.; Wilkin, Shevan (Elsevier BV, 2026)
Palaeoproteomic research has primarily concentrated on studying human bone, dentine, dental enamel, and calculus. In contrast, mummified soft tissue has not been extensively studied, limiting our understanding of what types of proteins can be recovered from these uncommonly preserved tissues. Here we use a published extraction protocol with an added bead-lysis step to increase protein recovery from mummified human tissues and LC-MS/MS to analyse a new dataset of three individuals from 18th-century Finland. We compare these data to three previously published datasets with samples from different tissue types, time periods, and taphonomic environments. Mummified soft tissue yielded a greater number of human immune proteins when compared to bone samples in general, and in particular when compared to archaeological bone. Overall, this study highlights the potential of soft tissue proteomics combined with more traditional methods for bioarchaeological research of disease and human-pathogen interactions.